1998
DOI: 10.1111/j.1524-4725.1998.tb04220.x
|View full text |Cite
|
Sign up to set email alerts
|

Alabaster Skin after Carbon Dioxide Laser Resurfacing with Histologic Correlation

Abstract: This patient experienced a profound expression of an increasingly recognized and reported complication of carbon dioxide laser resurfacing. Histologic correlation is similar to the results previously reported after phenol chemical peels, demonstrating a normal number of melanocytes but a decrease in epidermal melanin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 14 publications
(19 reference statements)
4
30
1
3
Order By: Relevance
“…Although absolute melanocyte numbers are not diminished by carbon dioxide resurfacing, the melanin synthesis pathway is functionally impaired in areas demonstrating hypopigmentation. 3 Possibly the discrepancy between the statement that nearly all patients experience hypopigmentation and the 13% incidence rate in this study reflects a difference in actual physical examination findings vs findings in a subsequent review of photographs only.…”
contrasting
confidence: 68%
“…Although absolute melanocyte numbers are not diminished by carbon dioxide resurfacing, the melanin synthesis pathway is functionally impaired in areas demonstrating hypopigmentation. 3 Possibly the discrepancy between the statement that nearly all patients experience hypopigmentation and the 13% incidence rate in this study reflects a difference in actual physical examination findings vs findings in a subsequent review of photographs only.…”
contrasting
confidence: 68%
“…[1][2][3][4][5][6] Generally, the QRL is used to treat epidermal and dermal pigmented lesions such as lentigines, ephelides, café-au-lait spots, Becker nevus, nevocellular nevi, Ota nevus, tattoos, and some cases of melasma. [7][8][9][10][11][12][13][14][15][16][17] However, after the removal of pigmented lesions with QRL irradiation, a recurrence of these lesions is frequently experienced. Although ultraviolet (UV) exposure may be causative of the recurrence of pigmented lesions, there is no experimental evidence to date that UV irradiation stimulates melanocytes and melanogenesis in the skin treated with QRL irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Further well-controlled, double-blind studies are required to evaluate the efficacy of hydroquinone for hyperpigmentation after laser resurfacing. It has been reported that hypopigmentation becomes evident 6 months after laser resurfacing and never recovers spontaneously without treatment, and that it may even prove fatal [15,22,23]. In our study, hypopigmentation appeared earlier, and faded within 1 year without treatment in most cases.…”
Section: Discussionmentioning
confidence: 47%